Increased Critical Thinking Ability through Problem Based Learning with Determining Factors - Slameto, Slameto (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Critical thinking is an essential ability for all aspects of human life. Learning practices in schools do not encourage critical thinking. The problem of this research are: 1) is the problem-based learning model developed in the feasible category? 2) How high is the level of critical thinking of students? 3) Among the factors: learning motivation, equilibration, and/ discipline, which one is the determinant? The method used is Research Development; this study collected data from 37 students participating in Learning Assessment Lectures from 2 classes. Data were collected using a rating scale consisting of 41 items, which tested valid and were 37 items reliable. Data processing assisted by SPSS version 25. This research successfully developed a Problem Based Learning Model that was declared feasible; Achievement of students' critical thinking skills at a high level. Obtained 2 models determining students' critical thinking skills. This finding is very useful for the management of education quality within the framework of the effectiveness and productivity of Higher Education Learning